Therapeutic activities of isopulegol related to Dentistry: in silico study (Research, Society and Development, 2020)
Objective: To describe the therapeutic activities of monoterpene (-)- isopulegol applied to dentistry through an in silico study. Methods: To conduct the study in the in silico model, the software for Prediction of Activity Spectra for Substances (PASS) was used online, which provides the probability of being active (Pa) and the probability of being inactive (Pb) of the compound in question. The activities presented by the software were determined for this research according to the criterion: probability of being active greater than 0.5, with significant performance in dentistry. Results: Eight therapeutic activities with satisfactory indices for dentistry were found, where some of these activities already have studies proving their effectiveness. Conclusions: It is concluded that the compound isopulegol has therapeutic potential mainly as a mucomembranous, anti-inflammatory, antiparasitic and antifungal agent, requiring further research such as in vitro and in vivo studies to better clarify the compound and its respective mechanisms of action.